Social Literacy in Social Studies Learning for Junior High School Students in Lahat City - Nawalinsi, Nawalinsi; Abdulkarim, Aim; Ruhimat, Mamat; Winarti, Murdiyah (JETL (Journal of Education, Teaching and Learning), 2024)
Social literacy is a competency that every person needs to master. Social literacy can be developed in social studies subjects in junior high schools so that it can equip students with knowledge, attitudes, and skills to interact with and contribute to their environment. This research aims to describe the level of social literacy achievement of students in social studies. The data collection method was carried out using a questionnaire instrument on Google Forms related to social literacy, totaling 21 items. Data analysis uses descriptive analysis. This research involved the research subjects of junior high school students in the city of Lahat. The number of samples taken was 206. The results of the research show that the social literacy level of junior high school students in Lahat City obtained different percentages: the intellectual skills indicator was 28.94, social skills was 16.33, cooperation skills were obtained on average 11.97, and attitudes and social values were obtained on average. became the indicator that obtained the highest percentage of 30.86. The conclusions of this research show that the social literacy abilities of junior high school students in Lahat City are the lowest on the cooperation skills indicator. The implication of the results of this research is that teachers can find out the social literacy level of their students, so they can design appropriate learning models and increase students' curiosity, so that students' social literacy levels become better.